2017
DOI: 10.1101/116517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The molecular link between auxin and ROS-Mediated polar root hair growth

Abstract: Root hair polar growth is endogenously controlled by auxin and sustained by oscillating levels of reactive oxygen species (ROS). These cells extend several hundred-fold their original size toward signals important for plant survival. Although their final cell size is of fundamental importance, the molecular mechanisms that control it remain largely unknown. Here we show that ROS production is controlled by the transcription factor RSL4, which in turn is transcriptionally regulated by auxin through several auxi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…These 151 results together highlight partially redundant but not identical roles of PRX1, PRX44 and PRX73 as 152 positive regulators of polar growth. This is in agreement with the negative effect of SHAM, which 153 blocks the peroxidase activities of most peroxidases, on root hair growth (Mangano et al 2017). 154 Therefore, we measured in vitro total peroxidase activity using a guaiacol oxidation-based assay and 155 found that prx01,44,73 roots showed reduced peroxidase activity (close to 50% reduction) ( Figure 156 1C) while PRXs OE lines showed enhanced activity, with a 40-50% increase in PRX73 OE and 157 approximately 20% increase in PRX44 OE (Figure 2E).…”
supporting
confidence: 88%
“…These 151 results together highlight partially redundant but not identical roles of PRX1, PRX44 and PRX73 as 152 positive regulators of polar growth. This is in agreement with the negative effect of SHAM, which 153 blocks the peroxidase activities of most peroxidases, on root hair growth (Mangano et al 2017). 154 Therefore, we measured in vitro total peroxidase activity using a guaiacol oxidation-based assay and 155 found that prx01,44,73 roots showed reduced peroxidase activity (close to 50% reduction) ( Figure 156 1C) while PRXs OE lines showed enhanced activity, with a 40-50% increase in PRX73 OE and 157 approximately 20% increase in PRX44 OE (Figure 2E).…”
supporting
confidence: 88%
“…This confirms that drastic changes in ROS-homeostasis controlled mostly by RBOHC inhibit auxin growth promoting effect. It was previously shown that the over-expression of either RSL4 or Auxin Response Factor 5 (ARF5) under the control of the root hair EXPANSIN 7 promoter (E7) led to high-levels of ROS (Mangano et al 2017). In addition, E7:RSL4 and E7:ARF5 were more insensitive to high Pi levels that Wt Col-0 and they developed almost regular extended root hairs ( Figure 1C ).…”
Section: Auxin Overcome Pi-repression Of Root Hair Growth In a Ros-dementioning
confidence: 99%
“…This result indicates that high expression of RSL4 or constitutive activated auxin signaling, both are able to partially repress the high levels of Pi-growth effect. To corroborate the ROS measurements performed with the H 2 DCF-DA probe as well as to determine if the main ROS molecule involved was hydrogen peroxide (H 2 O 2 ), we measured cytoplasmic H 2 O 2 ( cyt H 2 O 2 ) levels using a genetically encoded YFP-based H 2 O 2 sensor, HyPer (Mangano et al 2017). Similar results were obtained for high-levels of Pi that first repressed cytoplasmic H 2 O 2 while exogenous auxin was able to trigger an up-regulation of the ROS-signal in the presence of high-Pi in the root hairs ( Figure 1D ).…”
Section: Auxin Overcome Pi-repression Of Root Hair Growth In a Ros-dementioning
confidence: 99%
See 2 more Smart Citations